implementation of conical elements in double-pipe heat exchangers using CFD simulation. - Krouma, Youcef.; Lechelah. Seif Abou ElAlla. (University of Eloued جامعة الوادي, 2025)
Heat exchangers have gained significant economic importance. It is estimated that nearly all of the generated thermal energy passes through a heat exchanger at least once. The thermal-hydraulic properties of a double-pipe heat exchanger were analyzed with the aim of improving its performance. This study aims to improve the performance of a heat exchanger by implementing conical elements inside the inner pipe and analyzing their effect using CFD simulations. The goal is to increase heat transfer while keeping pressure drop low. Conical elements create turbulence, which helps transfer heat more effectively. However, too much turbulence may create resistance, making the system less efficient. Using CFD software ANSYS Fluent, this study tests a heat exchanger with different designs (simple, 25°, 45°, 60°) to find the best balance between higher heat transfer and lower pressure drop. We have concluded that the heat exchanger with 60° conical elements angle and velocity of 0.3 m/s performed better in terms of heat transfer and overall efficiency. The results will help design more efficient and cost-effective heat exchangers for industrial use..Les échangeurs de chaleur ont acquis une importance économique considérable. On estime que la quasi-totalité de l'énergie thermique produite traverse un échangeur au moins une fois. Les propriétés thermohydrauliques d'un échangeur à double tube ont été analysées afin d'améliorer ses performances. Cette étude vise à améliorer les performances d'un échangeur de chaleur en intégrant des éléments coniques dans le tube intérieur et en analysant leur effet à l'aide de simulations CFD. L'objectif est d'augmenter le transfert de chaleur tout en maintenant une faible perte de charge. Les éléments coniques créent des turbulences, ce qui favorise un transfert de chaleur plus efficace. Cependant, une turbulence excessive peut créer une résistance, réduisant ainsi l'efficacité du système. À l'aide du logiciel CFD ANSYS Fluent, cette étude a testé différents échangeurs de chaleur (simple, 25°, 45°, 60°) afin de trouver le meilleur équilibre entre un transfert de chaleur plus élevé et une perte de charge plus faible. Nous avons conclu que l'échangeur de chaleur avec des éléments coniques à 60° d'angle et une vitesse de 0,3 m/s offrait de meilleurs résultats en termes de transfert de chaleur et d'efficacité globale.
Master's thesis in energy
Keywords: H-E (Heat Exchanger); Double-pipe; Conical Elements; Heat Transfer; Turbulence; Échangeur de chaleur; Double tube; Éléments coniques